Pilotstudie för utformning av modell att uvärdera utrustning - Persson, Lisa (2012)
Swedish Trotting association was formed in 1925. They are the ones who design the regulations concerning what is permissible and not permissible for the horse, driver and trainer, when they have a license at a Swedish racing track. The Veterinary department of Swedish Trotting association decides in consultation with representatives from veterinaries around the country what is allowed and not allowed, based proven experience, combined with the availability of scientific data and Veterinary Department's own assessment.